Alteration of fecal microbiota by fucoxanthin results in prevention of colorectal cancer in AOM/DSS mice. (17th September 2020) - Terasaki, Masaru; Uehara, Osamu; Ogasa, Shinya; Sano, Taishi; Kubota, Atsuhito; Kojima, Hiroyuki; Tanaka, Takuji; Maeda, Hayato; Miyashita, Kazuo; Mutoh, Michihiro
Abstract: Fucoxanthin (Fx), a marine carotenoid found in edible brown algae, is well known for having anticancer properties. The gut microbiota has been demonstrated as a hallmark for colorectal cancer progression in both humans and rodents. However, it remains unclear whether the gut microbiota is associated with the anticancer effect of Fx. We investigated the chemopreventive potency of Fx and its effect on gut microbiota in a mouse model of inflammation-associated colorectal cancer (by azoxymethane/dextran sulfate sodium treatment). Fx administration (30 mg/kg bw) during a 14 week period significantly inhibited the multiplicity of colorectal adenocarcinoma in mice. The number of apoptosis-like cleaved caspase-3 high cells increased significantly in both colonic adenocarcinoma and mucosal crypts. Fx administration significantly suppressed Bacteroidlales (f_uc; g_ uc) (0.3-fold) and Rikenellaceae ( g_ uc) (0.6-fold) and increased Lachnospiraceae ( g_ uc) (2.2-fold), compared with those of control mice. Oral administration of a fecal suspension obtained from Fx-treated mice, aimed to enhance Lachnospiraceae, suppress the number of colorectal adenocarcinomas in azoxymethane/dextran sulfate sodium-treated mice with a successful increase in Lachnospiraceae in the gut. Our findings suggested that an alteration in gut microbiota by dietary Fx might be an essential factor in the cancer chemopreventive effect of Fx in azoxymethane/dextran sulfate sodium-treated mice. Abstract : Fucoxanthin altered gut microbiota with chemoprevention of inflammation-associated colorectal cancer in azoxymethane/dextran sulfate sodium-treated mice. Lachnospiraceae and Rikenellaceae are chemopreventive indictors in mice treated with Fucoxanthin. Administration of feces from Fucoxanthin-treated azoxymethane/dextran sulfate sodium-treated mice prevented mouse colorectal cancer.